The Correlation Between Motivation and Self-Care Mangement Among Leukemia Patients Based on Orem's Theory - Bakar, Abu; Pradanie, Retnayu; Kurniawati, Ninuk Dian; Zahra, Naili Raudiatus (Critical Medical and Surgical Nursing Journal, 2023)
Introduction: Leukemia is one of the most diagnosed types of cancer and a cause of death worldwide. Patients who experience severe side effects of cancer treatment tend to experience less than optimal self-care management. Leukimia patients in treatment often complain of fatigue, weakness, lack of energy, and nausea which hinder them in self-care management. The purpose of this study was to determine the relationship between motivation and self-care management. Methods: This study used an analytic descriptive research design with a cross sectional approach. Population on this research were members of Chronic Granulocytic Leukemia (it is known as "ELGEKA”), East Java, Indonesia. The sample size was 69 respondents using purposive sampling. The independent variable was motivation and the dependent variable was self-care management. Data was analyzed using Spearman Rho analysis with level of significance 0.05. Results: The results of this study indicated that there was a relationship between motivation and self-care management (p=0.000) and  (r=0,531). Discussion: Motivation has a significant relationship with self-care management in leukemia patients based on Orem's theory. The higher the motivation, the higher self-care management. Good self-care management involves nutrition and fluid management, physical activity, stress management, complementary therapy, information and support seeking, and medication adherence. Conclusion: Nurses have an important role in identifying and increasing patient motivation to carry out self-care management and changing their attitudes to improve health and disease care. The recommendation for future researchers is to develop research with interventions to improve self-care management in leukemia patients.